Visi Baru Konselor Sekolah dalam Rangka Meningkatkan Kualitas Layanan Pendidikan di Sekolah dan Madrasah - Ardimen Ardimen (Universitas Kanjuruhan Malang, 2018)
This study aims to describe the new vision of school counselors in order to improve the quality of education services. This study uses library research methods by reviewing reference books, scientific journals, documents, magazines, legislation and the results of similar studies accessed through an open journal system via internet search. The data collected was analyzed by using conten analysis techniques to obtain theories or concepts in answering the problem of this research. The results of the study show that the implementation of a new vision of school counselors can improve the quality of education services in schools and madrasah. To that end, the performance of the school counselor is no longer positioned in the relief effort to overcome the problem of students, but the counselor carries out counseling to help students who are undergoing the process of self-development in order to achieve optimal development, independence and happiness in living life. Among the new visions of the school counselor are; (1) academic focus/ student achievement, (2) building based on student strengths, (3) counselors as program leaders, planners and developers, (4) focusing on academic counseling, learning and achievement, and supporting student success, (5) counseling is an integral part of the education system, (6) counseling services focus on mission and role identification, (7) using data to influence change, etc.